Dialogues between history of science and history of the book: preliminary remarks - Haddad, Thomás A.S. (Circumscribere International Journal for the History of Science, 2015)
During most of the 20th century, history of science and the history of the book followed parallel, non-intersecting paths, with little occasion for a real cross‑fertilizing dialogue. Dueto its affiliation with the history of ideas, while history of science recognized the importance of books, it treated them as mere carriers of texts, being the conceptual analysis of the latter its genuine objective. In turn, history of the book paid little attention to the specificities of the scientific books and their world upon investigating print culture and its agents. In this paper I briefly review those parallel stories and indicate how, fortunately, both fields met in the 1980s (and more especially in the last two decades), resulting in a bourgeoning interdisciplinary field. I then give examples of the research in this field made by Brazilian scholars, which constitute the content of this dossier, showing how they are a part of the international surge of interest in this matter.